2016
DOI: 10.1016/j.foodres.2016.01.029
|View full text |Cite
|
Sign up to set email alerts
|

In vitro digestion of dairy and egg products enriched with grape extracts: Effect of the food matrix on polyphenol bioaccessibility and antioxidant activity

Abstract: The aim of this study was to evaluate the effect of the food matrix on polyphenol bioaccessibility and antioxidant activity during the in-vitro digestion of dairy and egg products enriched with grape extracts (GE). Four GE-enriched matrices produced under industrial conditions (custard dessert, milkshake, pancake and omelet) and the GE dissolved in water (control solution) were submitted to in vitro digestion and the bioaccessibility of the major classes of polyphenols as well as the evolution of the antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(51 citation statements)
references
References 39 publications
3
46
0
2
Order By: Relevance
“…Similar trend (loss in antioxidant capacity during intestinal digestion) was previously reported in the digestion of different foods (Carbonell-Capella et al, 2015;Celep et al, 2015;Rodríguez-Roque et al, 2013;Rodríguez-Roque et al, 2014). However, other studies have indicated a high antioxidant capacity of intestinal digested samples (Oliveira & Pintado, 2015;Pineda-Vadillo et al, 2016;Tagliazucchi et al, 2010), attributed to the deprotonation of the hydroxyl moieties present on the aromatic ring of the phenolic compounds due to the mild alkaline intestinal environment (Bouayed et al, 2011) or to the formation of derived products with a higher antioxidant capacity than that of their precursors (Pineda-Vadillo et al, 2016).…”
Section: Bioaccessibilitysupporting
confidence: 83%
See 2 more Smart Citations
“…Similar trend (loss in antioxidant capacity during intestinal digestion) was previously reported in the digestion of different foods (Carbonell-Capella et al, 2015;Celep et al, 2015;Rodríguez-Roque et al, 2013;Rodríguez-Roque et al, 2014). However, other studies have indicated a high antioxidant capacity of intestinal digested samples (Oliveira & Pintado, 2015;Pineda-Vadillo et al, 2016;Tagliazucchi et al, 2010), attributed to the deprotonation of the hydroxyl moieties present on the aromatic ring of the phenolic compounds due to the mild alkaline intestinal environment (Bouayed et al, 2011) or to the formation of derived products with a higher antioxidant capacity than that of their precursors (Pineda-Vadillo et al, 2016).…”
Section: Bioaccessibilitysupporting
confidence: 83%
“…In fact, the oral step lasts a few minutes, and polyphenol degradation is usually a time-depending process. Moreover, it has also been described that acid pH during the gastric step protects polyphenols against degradation (Pineda-Vadillo et al, 2016).…”
Section: Compound Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Their bioaccessibility must be considered first when evaluating the related nutritional efficacy, thus defining the term bioaccessibility as the fraction potentially available for absorption at the intestinal level. Recent studies have proved that this by‐product is an interesting source of bioactive compounds with applications in pharmacological, cosmetic and food industries, thanks to their bioactivity and technological characteristics (Pineda‐Vadillo et al ., ; Gil‐Sánchez et al ., ). For this reason, to deepen the knowledge about how these compounds may be efficiently absorbed into the circulation system appears sound.…”
Section: Wine Pomace Compositionmentioning
confidence: 99%
“…To overcome this issue, a standardized and practical static digestion model based on physiologically relevant conditions was proposed (Minekus et al, 2014). This model has already been used to study the bioaccessibility of certain polyphenols including anthocyanins (Pineda-Vadillo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%